Respuesta :

x^3 -4x^2 +7x -28 = x^2(x-4) +7(x -4) = (x^2 +7)(x-4)

so the 4th choice will be right sure 
frika

Consider polynomial [tex] x^3 - 4x^2 + 7x - 28. [/tex] You can group first two terms and last two terms:

[tex] x^3 - 4x^2 + 7x - 28=(x^3 - 4x^2) + (7x - 28). [/tex]

In first brackets the common factor is [tex] x^2 [/tex] and in second brackets the common factor is 7, then

[tex] x^3 - 4x^2 + 7x - 28=(x^3 - 4x^2) + (7x - 28)=x^2(x-4)+7(x-4)=(x-4)(x^2+7). [/tex]

Answer: the correct answer is D.

ACCESS MORE